2013
DOI: 10.1037/a0032335
|View full text |Cite
|
Sign up to set email alerts
|

Validation of data-driven computational models of social perception of faces.

Abstract: People rapidly form impressions from facial appearance, and these impressions affect social decisions. We argue that data-driven, computational models are the best available tools for identifying the source of such impressions. Here we validate seven computational models of social judgments of faces: attractiveness, competence, dominance, extroversion, likability, threat, and trustworthiness. The models manipulate both face shape and reflectance (i.e., cues such as pigmentation and skin smoothness). We show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
284
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(290 citation statements)
references
References 60 publications
3
284
3
Order By: Relevance
“…The images used to depict the trustee faces comprised of Caucasian male faces with neutral expressions that were all unique identities randomly generated and manipulated with FaceGen® 3.2 software (see Todorov et al, 2013). We selected 10 trustworthy and 10 untrustworthy faces that were +3 SDs and -3 SDs, respectively, from the neutral version of each face on a computer-modelled dimension of trustworthiness (see exemplar of face in Figure 1).…”
Section: Stimuli and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The images used to depict the trustee faces comprised of Caucasian male faces with neutral expressions that were all unique identities randomly generated and manipulated with FaceGen® 3.2 software (see Todorov et al, 2013). We selected 10 trustworthy and 10 untrustworthy faces that were +3 SDs and -3 SDs, respectively, from the neutral version of each face on a computer-modelled dimension of trustworthiness (see exemplar of face in Figure 1).…”
Section: Stimuli and Proceduresmentioning
confidence: 99%
“…The trustee faces in the study by Rezlescu et al (2012) were computer-generated faces based on mathematical models that enable a tightly controlled assessment of subtle variations in facial features that indicate trustworthiness (Todorov, Dotsch, Porter, Oosterhof, & Falvello, 2013). One such feature includes increased distance between the eyebrows and the eyes, which enhances perceived trustworthiness.…”
mentioning
confidence: 99%
“…For example, emotionless craniofacial features such as larger facial width-to-height ratio correlate strongly with perceptions of greater propensity for aggression (Carré et al, 2009; Stillman et al, 2010), reliably elicit inferences of threat from healthy individuals (Todorov et al, 2013), and account for variance in the amount of aggressive behavior demonstrated by men (Carré & McCormick, 2008). Detecting such latent and static facial signals of threat likely has noteworthy consequences, as appraisal of social threat is believed to facilitate behavioral responses when interacting with others (Bar et al, 2006, Green & Phillips, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, most databases do not provide stimuli that are distributed over a useful range of attractiveness. Among the very few databases of faces with controlled levels of attractiveness, one created by Todorov and colleagues consists of 25 computer-generated faces (not real human faces) varying on seven levels of attractiveness, and is freely available after completion of an agreement form (Todorov, Dotsch, Porter, Oosterhof, & Falvello, 2013). Another database (the Beautycheck project; Braun, Gruendl, Marberger, & Scherber, 2001) provides composite pictures derived from three or more original faces among neutral standardized pictures of 96 young adults (no original face available).…”
mentioning
confidence: 99%